Pengaruh Latihan Self-Talk Terhadap Kepercayaan Diri dan Peningkatan Hasil Dropshot pada Cabang Olahraga Bulutangkis - Helmi Akmal Fauzan; Komarudin Komarudin; Muhamad Tafaqur; Geraldi Novian (Jurnal Kepelatihan Olahraga, 2022)
In badminton self-confidence is an athlete's realistic expectation. In line with the badminton technique needed to support success in badminton. This study aims to examine the effect of self-talk training on self-confidence and increasing dropshot results in badminton. The method used in this study is an experimental method using a pretest posttest control group design. The sample in this study were 14 athletes from UPI badminton UKM taken from the population using purposive sampling technique, which were then divided into two equal groups, namely, the experimental group and the control group. The treatment in the form of self-talk exercises was given to the experimental group and conventional exercises were given to the control group for 4 weeks. The instrument used was a self-confidence questionnaire and a dropshot test which was given twice (pretest and posttest). Data analysis t test. The results showed that there was a significant effect of self-talk practice on self-confidence and increased dropshot results. In addition, there is a significant difference between self-talk and conventional training on self-confidence and increasing dropshot results in badminton. This study concludes that self-talk training is better than conventional training on self-confidence and increases dropshot results in badminton. The author suggests that the self-talk exercise method is used as training material and recommendations to increase self-confidence so that it can improve achievement.